Scoping literature review and focus groups with healthcare professionals on psychosocial and lifestyle assessments for childhood obesity care - L. W. Koetsier; E. van den Eynde; E. G. A. H. van Mil; M. van der Velde; R. de Vries; C. A. Baan; J. C. Seidell; J. Halberstadt (BMC, 2023)
Abstract Background Childhood obesity is a complex disease resulting from the interaction of multiple factors. The effective management of childhood obesity requires assessing the psychosocial and lifestyle factors that may play a role in the development and maintenance of obesity. This study centers on available scientific literature on psychosocial and lifestyle assessments for childhood obesity, and experiences and views of healthcare professionals with regard to assessing psychosocial and lifestyle factors within Dutch integrated care. Methods Two methods were used. First, a scoping review (in PubMed, Embase, PsycInfo, IBSS, Scopus and Web of Science) was performed by systematically searching for scientific literature on psychosocial and lifestyle assessments for childhood obesity. Data were analysed by extracting data in Microsoft Excel. Second, focus group discussions were held with healthcare professionals from a variety of disciplines and domains to explore their experiences and views about assessing psychosocial and lifestyle factors within Dutch integrated care. Data were analysed using template analysis, complemented with open coding in MAXQDA. Results The results provide an overview of relevant psychosocial and lifestyle factors that should be assessed and were classified as child, family, parental and lifestyle (e.g. nutrition, physical activity and sleep factors) and structured into psychological and social aspects. Insights into how to assess psychosocial and lifestyle factors were identified as well, including talking about psychosocial factors, lifestyle and weight; the professional-patient relationship; and attitudes of healthcare professionals. Conclusions This study provides an overview of psychosocial and lifestyle factors that should be identified within the context of childhood obesity care, as they may contribute to the development and maintenance of obesity. The results highlight the importance of both what is assessed and how it is assessed. The results of this study can be used to develop practical tools for facilitating healthcare professionals in conducting a psychosocial and lifestyle assessment.